The Partial Deinstitutionalization of Affirmative Action in U.S. Higher Education, 1988 to 2014 - Daniel Hirschman; Ellen Berrey (Sociological Science, 2017)
Since the 1990s, affirmative action opponents have targeted colleges’ and universities’ race-conscious admissions policies and secured bans on the practice in eight states. Although scholarly and media attention has focused on these dynamics at a handful of elite institutions, little is known about race-conscious admissions across the broader field of higher education. We provide a descriptive, quantitative account of how different types of colleges and universities responded to this political context. Through analysis of almost 1,000 selective colleges and universities, we find a dramatic shift in stated organizational policy starting in the mid-1990s. In 1994, 60 percent of selective institutions publicly declared that they considered race in undergraduate admissions; by 2014, just 35 percent did. This decline varied depending on status (competitiveness) and sector (public or private). Race-conscious admissions remain the stated policy of almost all of the most elite public and private institutions. The retreat from race-conscious admissions occurs largely among schools lower in the status hierarchy: very competitive public institutions and competitive public and private institutions. These patterns are not explained by implementation of state-level bans. We suggest that the anti–affirmative action movement had a diffuse impact whose effects varied across different strata of American higher education.